Customer Satisfaction with Commercial Airlines: The Role of Perceived Safety and Purpose of Travel - Ringle, Christian M.; Sarstedt, Marko; Zimmermann, Lorenz (Journal of marketing theory and practice, 2011)
This study investigates the customer satisfaction of airline passengers and introduces perceived safety as a satisfaction driver, which has not yet been considered in the literature. Applying structural equation modeling to data collected from a sample of airline passengers reveals that perceived safety is one of the key drivers that can explain the degree of overall customer satisfaction. This relationship is, however, strongly moderated by the purposes for which airline passengers travel (i.e., either for business or pleasure). Perceived safety has a significantly greater impact on the overall customer satisfaction of people who travel for pleasure than on that of business travelers, which implies that airlines should more strongly emphasize safety features in advertising aimed at leisure travelers.